The values for justice in the trade contract in Islamic Law - Sjaiful, Muh.; Nazar, Muh.; Zahrowati, Zahrowati (Technium Social Sciences Journal, 2022)
The trade contract made in writing has legal values that balance the right and obligation of the contracting parties. The most important in balancing the value of right and obligation, namely the values of justice. In the trade contract based on Islamic law, such as an example of the mudharabah contract, namely an agreement between the financier of capital (shahibul maal) and the recipient of capital (mudharib) who in the business, it can guarantee the justice of the parties. Justice is seen from the distribution of profit and losse. In the distribution of profit based on an agreement, while losse is determined if capital losse is only borne by the shahibul maal not by the mudharib. It provides justice if the loss of capital is only borne by the shahibul maal. It is unfair if the capital is borne by the mudharib since the mudharib in lost energy. Mudharib not get anything in the bussiness.